Problems of studying the Kalmyk people’s deportation by the Russian historigraphy - Ubushaev, Vladimir V. (The New Research of Tuva, 2009)
For a long time the tragedy of the deported people has been a taboo subject. In Russian historiography this problem has not been an object for a special research prior to the early 1990’s. For the several decades the very fact of deportation of the repressed people has been held back. An attempt to cover development of a historiography of a problem with the most typical publications is made in the article.